Chemodrug delivery using integrin-targeted PLGA-Chitosan nanoparticle for lung cancer therapy. Issue 1 (December 2017) - Babu, Anish; Amreddy, Narsireddy; Muralidharan, Ranganayaki; Pathuri, Gopal; Gali, Hariprasad; Chen, Allshine; Zhao, Yan; Munshi, Anupama; Ramesh, Rajagopal
Abstract In this study, we report the efficacy of RGD (arginine-glycine-aspartic acid) peptide-modified polylactic acid-co-glycolic acid (PLGA)-Chitosan nanoparticle (CSNP) for integrin αv β3 receptor targeted paclitaxel (PTX) delivery in lung cancer cells and its impact on normal cells. RGD peptide-modified chitosan was synthesized and then coated onto PTX-PLGA nanoparticles prepared by emulsion-solvent evaporation. PTX-PLGA-CSNP-RGD displayed favorable physicochemical properties for a targeted drug delivery system. The PTX-PLGA-CSNP-RGD system showed increased uptakevia integrin receptor mediated endocytosis, triggered enhanced apoptosis, and induced G2/M cell cycle arrest and more overall cytotoxicity than its non-targeted counterpart in cancer cells. PTX-PLGA-CSNP-RGD showed less toxicity in lung fibroblasts than in cancer cells, may be attributed to low drug sensitivity, nevertheless the study invited close attention to their transient overexpression of integrin αv β3 and cautioned against corresponding uptake of toxic drugs, if any at all. Whereas, normal human bronchial epithelial (NHBE) cells with poor integrin αv β3 expression showed negligible toxicity to PTX-PLGA-CSNP-RGD, at equivalent drug concentrations used in cancer cells. Further, the nanoparticle demonstrated its capacity in targeted delivery of Cisplatin (CDDP), a drug having physicochemical properties different to PTX. Taken together, our study demonstrates that PLGA-CSNP-RGD is a promising nanoplatform for integrin targeted chemotherapeutic delivery to lung cancer.